MANAJEMEN PEMBINAAN BAKAT DAN PRESTASI OLAHRAGA PESERTA DIDIK - Ramadhani, Ramadhani; Simanjuntak, Victor G; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The problem in this research is how much the involvement of teacher penjasorkes in management of talent development and sports achievement of learners. The purpose of this study is to determine the involvement of teacher penjasorkes in the management of talent and sports achievement learners. The method used in this research is descriptive survey method using questionnaire-shaped research instrument. The population in this study is all teachers penjasorkes SMAN level in Pontianak City, amounting to 18 people. In this study the determination of samples using saturated sampling technique that is by taking the entire population, the sample used in this study is all penjasorkes teachers. Data analysis was done by using descriptive analysis technique percentage. The results showed that the management of sports talent coaching by the teacher of penjasorkes showed that 9 teachers (50%) were included in the low category and for the sports achievement of the students by the penjasorkes teacher showed that 7 teachers (38.89%) were included in the low category. Keywords: Management, Development, Sport Achievement